2017
DOI: 10.4171/zaa/1581
|View full text |Cite
|
Sign up to set email alerts
|

On the Persistence of the Eigenvalues of a Perturbed Fredholm Operator of Index Zero under Nonsmooth Perturbations

Abstract: Let H be a real Hilbert space and denote by S its unit sphere. Consider the nonlinear eigenvalue problem Lx + εN (x) = λx, where ε, λ ∈ R, L : H → H is a bounded self-adjoint (linear) operator with nontrivial kernel and closed image, and N : H → H is a (possibly) nonlinear perturbation term. A unit eigenvectorx ∈ S ∩ Ker L of L (corresponding to the eigenvalue λ = 0) is said to be persistent if it is close to solutions x ∈ S of the above equation for small values of the parameters ε = 0 and λ. We give an affir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…There are useful relations between the various constants introduced so far, that can be easily obtained by the definitions and are shown for instance in [4,6,17]. We report here, for further use in the present paper, only the following:…”
Section: A Simplified Spectrummentioning
confidence: 90%
See 2 more Smart Citations
“…There are useful relations between the various constants introduced so far, that can be easily obtained by the definitions and are shown for instance in [4,6,17]. We report here, for further use in the present paper, only the following:…”
Section: A Simplified Spectrummentioning
confidence: 90%
“…We remark that in general, the study of the measure of noncompactness in Banach spaces forms a vast and active research field in Functional Analysis, that has received further interest and expansion from the axiomatic approach presented in [16]; for an updated overview of this, see for instance [18] and the references therein. While in particular, the importance of ω for the study of nonlinear operators, originally shown in [6], has been further demonstrated especially in works by M. Furi and his school, see for instance their recent paper [17]. One basic property of ω(F) that we shall use repeatedly in Section 3 is expressed by the following statement (see [6], Proposition 3.1.3), the proof of which will be given there for the reader's convenience: if ω(F) > 0, then F is proper on closed bounded sets; that is, given any compact K ⊂ X and any closed bounded…”
Section: A Simplified Spectrummentioning
confidence: 96%
See 1 more Smart Citation
“…After the result of Chiappinelli, in a series of papers [6,[8][9][10][11] the above property of "local" persistence of the eigenvalues and eigenvectors was extended to the case in which the multiplicity of the eigenvalue λ 0 is bigger than one. In this case the set of unit eigenvectors of L corresponding to λ 0 is the (n − 1)-dimensional unit sphere S n−1 = S ∩ Ker(L − λ 0 I ), where S is the unit sphere in H , I is the identity of H and n is the multiplicity of λ 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the results of the recent papers [6,11] are obtained in the more general context of real Banach spaces. To better explain these results, consider the system…”
Section: Introductionmentioning
confidence: 99%